Microstructural and mineralogical analysis of greenschist-facies deformation in the eastern Yukon-Tanana terrane, Yukon, Canada - Lindsay, Cassis (School of Earth, Environment and Society, 2022)
The Yukon-Tanana terrane of the northern Canadian Cordillera experienced multiple episodes of mafic-intermediate volcanism during the Paleozoic, followed by polyphase deformation during its accretion to the North American continent. This study seeks to analyse the deformation history of a heterolithic greenschist unit that is exposed near the Boswell River in south-central Yukon. This greenschist unit, which is coincident with an aeromagnetic high, includes thinly layered intervals that exhibit centimeter to meter-scale folds and crenulations. Using an oriented greenschist facies sample collected from a meter-scale fold during field mapping, a detailed microstructural approach was applied to determine the number and nature of deformation events recorded in the area. Subsequent petrographic analysis was conducted to identify the minerals present and establish the temperature during deformation. Observations show that the main mineral phases are quartz-muscovite-chlorite, in addition to a variety of sulphide minerals, some of which show compositional zonation. A fracture runs through the slide, bearing crushed mica along one border, possibly indicative of shear. Based on these observations, it was established that the sample records at least three distinct stages of deformation. To further constrain the deformation history, use of a scanning electron microscope (SEM) was employed to link the observations to the larger-scale tectonic evolution of the area.
Keywords: Yukon, geology, mineralogy, Yukon-Tanana terrane